Influence of ethanol-wet dentin, adhesive mode of application, and aging on bond strength of universal adhesive - SOUZA,Mauricio Yugo de (2018)
Abstract The aim of this study was to evaluate the effect of ethanol on the bond longevity of a universal adhesive system to bovine dentin, under different modes of adhesive application and artificial aging. Bovine dentin was exposed, and the smear layer was standardized by sandpaper polishing. Specimens were randomly divided into 2 groups: ethanol (E) and non-ethanol (N). Groups were subdivided according to adhesive mode of application into etch-and-rinse (Er) and self-etching (S). Resin blocks were built onto the treated surface, and the specimens were stored in deionized water at 37°C for 48 h. Half of the specimens (n = 10) were subjected to thermomechanical aging (A for aged and Na for non-aged). Resin/dentin beams were obtained and subjected to microtensile test in a universal testing machine. Data were analyzed using a three-way ANOVA and Tukey’s tests (α = 5%). There was interaction among the three factors (p=0.0003). The use of ethanol resulted in higher values, except for the Er and Na groups (E_Er_Na = N_Er_Na). The mode of application was similar, except for the N and A groups (N_S_A > N_Er_A). For the A groups, the values were lower, except in the cases using ethanol, in which the results were not affected. The study concluded that the use of ethanol resulted in higher microtensile bond strength values, even after aging. The mode of adhesive application did not influence the results.